TRANSLATING TABOO SPEECH ACT IN THE OMAR SERIES: A PRAGMATIC AND TECHNIQUE-BASED ANALYSIS OF ARABIC-INDONESIAN SUBTITLES - Solihat, Siti Roisah; Al Farisi, Mohamad Zaka; Saleh, Nalahuddin (Universitas Islam Sumatera Utara (UISU), 2025)
Understanding the translation of taboo speech acts in audiovisual media is essential, particularly in contexts involving differing cultural norms and values. This study analyzes the translation strategies used to render taboo speech acts from Arabic into Indonesian in the Omar series. A descriptive qualitative approach was adopted using an embedded case study design. The data comprise 26 Arabic taboo utterances and their corresponding Indonesian subtitles. These utterances were categorized into nine types based on Jay’s (2009) typology, with the most frequent being insults related to perceived psychological, physical, or social deviations (19.2%). The translation techniques were examined using Molina and Albir’s (2002) framework, which revealed that reduction (25%) was the most applied strategy. A combination of single, double, and triple-technique applications was also observed across the dataset. These findings suggest that subtitles prioritize cultural acceptability over literal equivalence, employing strategies that mitigate potential offense while preserving the communicative intent of the source text.